2001
DOI: 10.1590/s0102-09352001000300018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da imunodeficiência severa combinada em cavalos da raça Árabe em plantéis de Minas Gerais e São Paulo

Abstract: Neste estudo foram genotipados 205 cavalos da raça Árabe, criados nos estados de Minas Gerais e São Paulo, via DNA por meio de PCR, para determinação da presença do gene mutante SCID. Os resultados mostraram 98,5% de animais normais (202/205) e 1,5% de portadores (3/205). Pela análise da genealogia dos portadores identificados pode-se, ainda, confirmar a participação de um garanhão anteriormente identificado como provável disseminador da doença.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Several previous genetic studies have investigated the five nucleotide deletion in the DNA-PKcs gene using primers that yield a PCR product of 521 bp [25], 259 bp [15], 235 bp [16], 179 bp [10], 174 bp [22], 169 bp [8,26], 163 bp [1,9,19,27], 162 bp [11], and 135 bp [13,17] in different Arabian horse populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous genetic studies have investigated the five nucleotide deletion in the DNA-PKcs gene using primers that yield a PCR product of 521 bp [25], 259 bp [15], 235 bp [16], 179 bp [10], 174 bp [22], 169 bp [8,26], 163 bp [1,9,19,27], 162 bp [11], and 135 bp [13,17] in different Arabian horse populations.…”
Section: Discussionmentioning
confidence: 99%
“…To detect wild and mutant SCID alleles, the amplified PCR products were electrophoresed on 10% [10], 8% [13,15], and 6% Polyacrylamide gel [8,27], 4% agarose gel [17], or capillary electrophoresis [9,11,16,19]. In addition to electrophoresis, sequencing analysis could be performed to identify the genotypes of a population in terms of the presence/absence of SCID mutant alleles, as in these studies [1,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After development of reliable and useful DNAbased tests, contemporary incidence values of SCID carrier and clinically affected foals have been increasingly reported from different countries (3,11,14,21,20,22,26). For example, it is reported that 17 of 204 (8.3%) foals are found SCID affected in Australia (11).…”
Section: Discussionmentioning
confidence: 99%